Zinc in soil, plant and human health: a review (Research, Society and Development, 2020)
It is estimated that 17.3% of the world population is at risk for Zn deficiency, and annually, about half a million children under five years of age die from causes related to Zn malnutrition. Low-cost strategy to increase Zn intake by humans is to increase the consumption of biofortified crops. Biofortification comprises the process for increasing contents of one or more nutrients in the edible parts of agricultural crops in order to increase their nutritional value. For biofortification to reach one billion people by 2030, mutual efforts must be added. Among them, policies must place more emphasis on agriculture role in improving health. Governments and institutions must include biofortification on food security policy, and food processors and others responsible for production chain must include biofortified crops in their product lines. The objective of this study was to carry out a bibliographic review to elucidate the dynamics of Zn in soil, the essential function of Zn in plant yield, the plant role in transfer Zn to human body, the importance of Zn in the human health and current measures that have been taken to mitigate Zn malnutrition in the world.